Analisis Askep dengan Penerapan Teknik Relaksasi Genggam Jari terhadap Skala Nyeri Pasien Post Operasi Hernioraphy - Puput Endah.R; Aniska Indah Fari; Novita Elisabeth Daeli (Lembaga Pengembangan Kinerja Dosen, 2025)
A hernia is a protrusion of the abdominal wall into another body cavity (hip or pelvis, chest or thorax). One of the procedures performed in cases of hernia is surgery called herniorrhaphy. Surgery is an invasive treatment procedure through incisions to open the part of the body that will be treated surgically, which will cause pain. The pain felt after surgery is acute pain. Acute pain can complicate the healing process which can hinder the patient's ability to mobilize, rehabilitate and be hospitalized. One of the non-pharmacological therapies used to reduce pain is finger-hold relaxation therapy. Finger grip relaxation is a simple technique that combines breathing and holding a hand on each finger which can help control emotions and stress. It is hoped that this method can stimulate the brain to produce positive hormones and reduce cortisol secretion so that pain is reduced. Finger grip therapy intervention can help patients reduce the scale of pain felt after surgery. The case study used a descriptive method with a nursing process approach which was carried out on 3 respondents aged 67 - 76 using a One Group Pretest Posttest research design which was measured using the NRS instrument for 3 days. The results showed that there was a decrease in the pain scale in respondents after being given finger grip relaxation therapy.